Comparison of bubble removal performances of five membrane oxygenators with and without a pre-filter. (April 2023) - Ishida, Mitsuru; Takahashi, Sho; Okamura, Homare
When employing minimal invasive extracorporeal circulation (MiECC), the removal of bubbles in the circuit is important to prevent air embolism. We investigated the bubble removal performance of the FHP oxygenator with a pre-filter and compared it with that of four oxygenators, including the Fusion oxygenator, Quadrox oxygenator, Inspire oxygenator, and FX oxygenator. A closed test circuit filled with an aqueous glycerin solution was used. Air injection (10 mL) was performed prior to the oxygenator, and the number and volume of the bubbles were measured at the inlet and outlet of each oxygenator. At the inlet of the five oxygenators, there were no significant differences in the total number of bubbles detected. At the outlet, bubbles were classified into two groups according to the bubble size: ≥100 μm and <100 μm. Tests were performed at pump flow rates of 4 and 5 L/min. For bubbles ≥100 μm, which are considered clinically detrimental, the FHP was the lowest number and volume of bubbles at both pump flow rates compared to the other oxygenators. Regarding the bubbles <100 μm, the number of bubbles was higher in the FHP than those in others; however, the volume of bubbles was significantly lower at 4 L/min and tended to be lower at 5 L/min. The use of the FHP with the pre-filter removed more bubbles ≥100 μm in the circuit than that by the other oxygenators. Graphical Abstract